The hidden problems of illegal abortions in Thailand - Chinthakanan, Orawee; Rochat, Roger W.; Morakote, Nuntana; Chaovisitseree, Somsak (Biomedical Sciences and Clinical Medicine, 2024)
High rates of unplanned pregnancy and induced abortion were reported among young women in Thailand. Complications from illegal and low standard abortion are a current major health problem in the country. Abortion is considered to be a life-destroying act that counts as a serious bap (sin or demerit) in Thai culture. The current abortion law in Thailand stipulates that abortion is illegal except when performed by a medical practitioner in circumstances considered necessary when the pregnancy endangers the woman’s health or conception had occurred during a sexual offense such as rape or incest. However, most Thai people feel that the abortion law should be amended because Thai society has changed radically in its attitudes over the past decade. The debate over legal reform of this law is still active. Thailand needs a multi-disciplinary approach to reduce and prevent the number of unplanned pregnancies and unsafe abortions, with special attention paid to the most vulnerable group of women.